Spatial Dynamics of a Lattice Lotka-Volterra Competition Model with a Shifting Habitat (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we concern with the spatial dynamics of the latticeLotka-Volterra competition system in a shifting habitat. We study the impact of the environmental deterioration rate on the population density underthe strong competition condition. Our results show that if the environmentdeteriorates rapidly, both species will become extinct. However, when theenvironmental degradation rate is not so fast, the species with slow diffusionwill go extinct, while those with fast diffusion will survive. The extinctionof species with slow diffusion can be divided into two situations: one is theextinction caused by environmental deterioration faster than its own diffusionspeed, the other is the extinction caused by slow diffusion speed under theinfluence of strong competition.
Keywords: Lattice Lotka-Volterra competition model; shifting habitat; spreading speed.